Identification of sex chromosomes in Eremias velox (Lacertidae, Reptilia) using lampbrush chromosome analysis - Artem P. Lisachov; Svetlana A. Galkina; Alsu F. Saifitdinova; Svetlana A. Romanenko; Daria A. Andreyushkova; Vladimir A. Trifonov; Pavel M. Borodin (Comparative Cytogenetics, 2019)
Reptiles are good objects for studying the evolution of sex determination, since they have different sex determination systems in different lineages. Lacertid lizards have been long-known for possessing ZZ/ZW type sex chromosomes. However, due to morphological uniformity of lacertid chromosomes, the Z chromosome has been only putatively cytologically identified. We used lampbrush chromosome (LBC) analysis and FISH with a W-specific probe in Eremias velox (Pallas, 1771) to unequivocally identify the ZW bivalent and investigate its meiotic behavior. The heterochromatic W chromosome is decondensed at the lampbrush stage, indicating active transcription, contrast with the highly condensed condition of the lampbrush W chromosomes in birds. We identified the Z chromosome by its chiasmatic association with the W chromosome as chromosome XIII of the 19 chromosomes in the LBC karyotype. Our findings agree with previous genetic and genomic studies, which suggested that the lacertid Z chromosome should be one of the smaller macrochromosomes.